Efektivitas Penerapan Sistem Administrasi Keuangan Sederhana Terhadap Akurasi Pencatatan Keuangan Operasional Karyawan - Ratu Chaterine Fajri; Arif Makhsun; Nelly Suryani; Putri Irmala Sari; Supri Yanto; Sinar Putri (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
Micro, Small and Medium Enterprises (MSMEs) in the culinary sector, particularly kebab stalls, often face limitations in managing financial administration in an orderly and structured manner. Kebab Mas Yul is one of the growing culinary businesses in a residential area that relies on daily workers without adequate knowledge of financial recording. This community service activity aims to increase employee capacity in recording daily operational financial transactions through training on a simple financial administration system based on manual forms and cash books. The method used is participatory action research with stages of problem identification, instrument design, training, mentoring, and evaluation. The results showed an increase in employee understanding of basic financial recording principles by 78% and the formation of consistent daily recording habits within a one-month program implementation period. The simple system proved capable of reducing daily cash discrepancies and supporting sustainable business accountability.